Fatigue behavior of PVD coated Ti-6Al-4V alloy - Costa, M. Y. P. [UNESP]; Venditti, M. L. R. [UNESP]; Cioffi, M. O. H. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Guimaraes, V. A. [UNESP]; Ruas, R. (Elsevier B.V., 2011)
The aim of the present work is to identify an environmentally clean coating process that will present lower influence in the Ti-6Al-4V fatigue strength. Axial fatigue tests of Ti-6Al-4V alloy TiN, CrN and WC:H (tungsten containing diamond-like carbon) Physical Vapor Deposition (PVD) coated was evaluated. Decrease in fatigue life was observed for coated specimens in comparison to base metal. Scanning Electron Microscopy technique was used to observe crack origin sites and coating thickness. DLC coating provides higher Ti-6Al-4V alloy PVD coated fatigue strength due to lower defects presence and the chromium interlayer, which acts as a barrier to fatigue crack propagation. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Fatigue strength; Titanium alloys; PVD coatings